Policy regime and policy change: Comparing the phenomenon of local government before and after regional autonomy - Kamaludin Kamaludin; Berto Usman (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2018)
This research aims to evaluate the financial performance of four municipalities (Bengkulu City, Rejang Lebong Regency, South Bengkulu Regency, and North Bengkulu Regency) in Bengkulu Province, Indonesia. The study also identifies the contribution of several financial variables before and after the implementation of regional autonomy. Theoretically, regional autonomy enables these four municipalities to manage their Local Own-Source Revenue (LOSR or PAD - Pendapatan Asli Daerah) better because these municipalities now have to learn to manage their financial resources independently. However, the findings indicate that these four municipalities still exhibit a high financial dependency on the central government or the fiscal balance fund. Consequently, the contribution of LOSR to the total income is still low. Besides, the study finds that these four municipalities exhibit a sufficiently good efficiency ratio but a fluctuating LOSR growth ratio, especially in some municipalities before the proliferation of new municipalities. Further, the main variables of the degree of financial decentralization, local financial autonomy, efficiency, and LOSR growth do not exhibit significant differences between the pre- and post- regional autonomy implementation.